(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Background: Intraocular pressure (IOP) is one of the most important parameters in the diagnosis and treatment of glaucoma. Glaucoma has been established as the second leading cause of blindness. The treatment of glaucoma focuses mainly on lowering intraocular pressure (IOP). The target IOP is often set to a level 20% to 30% of IOP reduction, and consequent large IOP reduction beyond 30% or even 40% in cases of advanced glaucoma The different methods of tonometery are: Goldman Applanation tonometery, Noncontact (air-puff) tonometery, Perkins tonometery, Tonopen tonometery, Transpalpebral tonometery. Objective: To determine the frequency of accuracy of intraocular pressure (IOP) measured by non-contact (air puff) tonometer compared with Goldmann applanation tonometer. Methods: This was a non-interventional, cross sectional study conducted at a tertiary care centre of Dhaka, Bangladesh. consecutive subjects attending the BSMMU eye OPD were included in the study. IOP was measured by non-contact (air puff) tonometer and a slit lamp mounted GAT in all the subjects. The study samples were selected by convenience sampling who presented for check-up in the Eye Department of community ophthalmology, Bangabandhu Sheikh Mujib Medical University, Dhaka. Bangladesh. Results:A total of 120 eyes in 60 patients were studied. The mean age of the patients was 41.60 year. study population consisted of 24 (40 %) men and 36 (60 %) women. The mean intraocular pressure was 13.52 &13.72 mmHg for GAT, and 16.64 & 17.44 mmHg for Air puff respectively. The range of measurements by GAT was from 10 to 23 mmHg and by Air puff was 12 to 28mmHg. The difference between IOP measured by two instruments were statistically significant (p=0.000). Conclusion: Airpuff tonometer is quick, a non-contact method to measure intraocular pressure and is useful for screening purposes and postoperative case but the measurements should be confirmed with Goldmann applanation tonometer for accurate labelling of intraocular pressure.